Transactions on Modularity and Composition I - Chiba, Shigeru; T. Leavens, Gary; Ziarek, Lukasz; Eugster, Patrick; Südholt, Mario (Springer Nature, 2016)
The LNCS Transactions on Modularity and Composition are devoted to all aspects of software modularity and composition methods, tools, and techniques, covering requirement analysis, design, implementation, maintenance, and evolution. The focus of the journal also includes modelling techniques, new paradigms and languages, development tools, measurement, novel verification and testing approaches, theoretical foundations, and understanding interactions between modularity and composition. This, the first issue of the Transactions on Modularity and Composition, consists of two sections. The first one, guest edited by Patrick Eugster, Mario Südholt, and Lukasz Ziarek, is entitled "Aspects, Events, and Modularity" and includes papers focusing on context-oriented software development, specifications for even-based systems, and development of modular software. The second section, guest edited by Gary T. Leavens, contains journal versions of selected papers from Modularity 2015, which was held in March 2015, in Fort Collins, Colorado, USA. Topics covered by the papers in this section include software unbundling, layer activation in context-oriented programming, modular reasoning in event-based languages, and dynamic dispatch for method contracts using abstract predicates.